2015
DOI: 10.2319/112514-843.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corticision on root resorption with heavy and light forces

Abstract: At day 14, neither the amount of force nor the cortical incision caused significant effect on root resorption that was registered by histomorphometric or microCT analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…This finding was in contrast to previous studies. Murphy et al 11 did not find a significant difference in resorption between corticision-assisted tooth movement with forces of 10 g (light force) and 100 g (heavy force) at 14 days. This contradictory result possibly came from the different experimental period.…”
Section: Discussionmentioning
confidence: 90%
“…This finding was in contrast to previous studies. Murphy et al 11 did not find a significant difference in resorption between corticision-assisted tooth movement with forces of 10 g (light force) and 100 g (heavy force) at 14 days. This contradictory result possibly came from the different experimental period.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have mostly investigated root resorption as a result of surgical insult, but no studies have reported the correlation between the increase of surgical insult and orthodontically induced root resorption. [13][14][15] The results suggested the amount of orthodontically induced root resorption was directly associated with the extent of injury.…”
Section: Discussionmentioning
confidence: 96%
“…The blade should be pulled out by a swing motion. Clinical studies were conducted on humans [32] and animals [31,33] and concluded corticision effectively fastens tooth movement similar to corticotomy and is advantageous because of its less invasiveness. Among the published studies on cortision two were case control studies [31,33] and other was case series [31,32].…”
Section: Surgical Methodsmentioning
confidence: 99%
“…Clinical studies were conducted on humans [32] and animals [31,33] and concluded corticision effectively fastens tooth movement similar to corticotomy and is advantageous because of its less invasiveness. Among the published studies on cortision two were case control studies [31,33] and other was case series [31,32].Piezocision: This is a minimally invasive procedure involves flapless in combining piezosurgical cortical micro-incisions with selective tunneling that allows for soft-tissue or bone grafting.[34] Vercelotti and Podesta [35] established the use of piezosurgery instead of burs, in conjunction with the conventional flap elevations to create an environment conducive for the rapid tooth movement. This technique is quite invasive as it requires extensive flap elevation and osseous surgeries, with post-surgical discomfort.…”
mentioning
confidence: 99%